2019
DOI: 10.1080/21691401.2018.1554579
|View full text |Cite
|
Sign up to set email alerts
|

mPEG-icariin nanoparticles for treating myocardial ischaemia

Abstract: Icariin (ICA), a major active ingredient from Chinese medicine, has unique pharmacological effects on ischaemic heart disease. However, its hydrophobic property limits its administration and leads to poor efficacy. This work aimed to change its hydrophobic property and improve the treatment efficacy. We designed a new nano-drug to increase the ICA delivery. ICA was modified with hydrophilic polyethylene glycol monomethyl ether (mPEG) by a succinic anhydride linker to form a polyethylene glycol-icariin (mPEG-IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In the dialysis bag method, pre-weighed samples of pure-ICA and ICA-phytosomes (equivalent to 1 mg ICA) were introduced separately into two pre-soaked dialysis bags (molecular weight cut-off (MWCO) of -14 KDa; Sigma-Aldrich, St. Louis, Missouri, USA). The release was performed in 100 mL of phosphate-buffered saline (PBS) buffer pH 7.4 at 37 ± 0.5 • C with continuous stirring at 100 rpm using a magnetic stirrer [35]. Samples were withdrawn at time points of 0.5, 1, 2, 4, 6, 8, and 12 h and immediately replaced with equivalent amount of fresh medium.…”
Section: In Vitro Releasementioning
confidence: 99%
“…In the dialysis bag method, pre-weighed samples of pure-ICA and ICA-phytosomes (equivalent to 1 mg ICA) were introduced separately into two pre-soaked dialysis bags (molecular weight cut-off (MWCO) of -14 KDa; Sigma-Aldrich, St. Louis, Missouri, USA). The release was performed in 100 mL of phosphate-buffered saline (PBS) buffer pH 7.4 at 37 ± 0.5 • C with continuous stirring at 100 rpm using a magnetic stirrer [35]. Samples were withdrawn at time points of 0.5, 1, 2, 4, 6, 8, and 12 h and immediately replaced with equivalent amount of fresh medium.…”
Section: In Vitro Releasementioning
confidence: 99%
“…Many studies have demonstrated that icariin, a polyphenol flavonoid (Meng et al, 2015), protects cardiomyocytes from injury and, therefore, elicits cardioprotective effects (Ke et al, 2015;Zheng et al, 2019). Interestingly, we found that icariin restored the cardiac function in DCM, as demonstrated by the decrease in LVEF and LVFS ( Figures 1A, B) and the evident increase in LVEDD and LVESD ( Figures 1C, D).…”
Section: Discussionsupporting
confidence: 50%
“…H9c2 cardiomyocytes were digested with 0.25 g/L trypsin (Gibco) at approximately 80% cell confluence to be used for subculturing (Y. Zheng et al, 2019 ). The cells were seeded in 25-cm 2 culture flasks and passaged every 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were observed and photographed immediately under fluorescence microscopy (Leica, Germany) (Y. Zheng et al, 2019 ). Nuclei with brightly stained and bright fragments were regarded as apoptotic cells, while cells with blue chromatin and organized structure were considered to be normal.…”
Section: Methodsmentioning
confidence: 99%